Oral administration of Costa Rican guava (Psidium friedrichsthalianum) juice induces changes in urinary excretion of energy-related compounds in Wistar rats determined by 1H NMR - Montoya Arroyo, Alexander (2020)
Introduction: Psidium friedrichsthalianum fruits have in vitro antioxidant activity and their intake has been suggested to have potential health benefits; however, there is still no evidence on the potential in vivo effect of their consumption. Objective: We aim to study the effect of the oral administration of a P. friedrichsthalianum juice on the urinary metabolome of adult male Wistar rats. Methods: Acute and short-term interventions were carried out and urine sample metabolites were analyzed in a 600 MHz NMR instrument with a NOESY-presat sequence.and post-treatment effects were identified by comparison against control conditions. Results: Acute administration caused a decrease in the excretion of citrate and allantoin in the 0 to 6 h period and citrate and α-ketoglutarate in the 6 to 12 h period. Lactate and Krebs cycle intermediates showed reduced excretion in the 12 to 24 h period. Short-term administration (for 7 days) decreased the excretion of Krebs cycle intermediates together with lactate and allantoin. The effect was stronger after short-term administration suggesting a dose-dependent effect. Conclusion: P. friedrichsthalianum juice caused a change in rat excretion of energy metabolites, probably associated with an increase in aerobic metabolism, suggesting in vivo modulation of the redox balance.